Some new research about Vlaicu network during the Second World War - Marian Zidaru (Technium Social Sciences Journal, 2020)
George Beza (1907-1997) joined the Iron Guard. He acquired the title “Commander” of the legion but soon left the organization. He worked for a while with Mihai Stelescu (excluded from the Iron Guard on September 25, 1934) to publish the magazine "Crusade of Romanism", in which they criticized the legion. In April 1936, he and Stelescu were placed on the watch list of those who were to be punished for their treachery. Beza joined PN? and played and played an important role in World War II a monument was erected in Jerusalem in honor of Beza. He played an important role in the plans of SOE to organize anti-Antonescu propaganda in Romania. He was the author of the Vlaicu anti-axis resistance in Romania. This paper presents some aspects of SOE’s organizational activities related to the Vlaicu program.